The father-daughter plot : Japanese literary women and the law of the father - Copeland, Rebecca L., 1956-; Ramirez-Christensen, Esperanza U. (University of Hawai'i Press, 2001)
This provocative collection of essays is a comprehensive study of the "father-daughter dynamic" in Japanese female literary experience, Its contributors, representing a new generation of scholars of Japanese literature, examine the ways in which women have been placed politically, ideologically, and symbolically as "daughters" in a culture that venerates "the father." They weigh the impact that this daughterly position has had on both the performance and production of women's writing from the classical period to the present